A study of some aspects of student teaching practices prevalent in the Sinhala-medium primary teacher training institutions in Ceylon - Ranasinghe, Amara Dayawathie 1925- (Quezon City s.n., 1969)
The purpose of the study is to make an objective analysis of the contemporary student teaching practices in the Sinhala-medium Primary Teacher Training Institutions (teacher colleges) in Ceylon through a comparative survey approach in order to make suggestions for improvement of existing student teaching practices in Ceylon.
Thesis (Master of Education)--University of the Philippines
Keywords: Student teaching -- Ceylon